A 12-week intramuscular toxicity study of risperidone-loaded microspheres in Beagle dogs. (May 2014) - Tian, J; Wang, W; Ye, L; Cen, X; Guan, X; Zhang, J; Yu, P; Du, G; Liu, W; Li, Y
Long-acting formulations of antipsychotics are important treatment options to increase the compliance of schizophrenic patients. Risperidone, a 5-HT2 and dopaminergic D2 receptor antagonist, was developed as long-acting sustained-release microspheres with poly(lactide-co-glycolide) (PLGA) as a drug carrier for the treatment of schizophrenia. In the present study, the main objective is to determine the nonclinical safety profile of risperidone-loaded microspheres (RM) in Beagle dogs after intramuscular administration for 3 months, once in 2 weeks, followed by 8-week recovery phase. No animal death was found and no special toxicological findings were observed. The findings, such as hypoactivity, ptosis, increased heart rate, and elevated serum and pituitary prolactin levels, were observed and related to the pharmacological effects of risperidone. The changes in the reproductive system (uterus, ovary, vagina, cervix, and mammary gland) were considered secondary to the prolactin elevation, and the congestion of spleen was related to risperidone. The foreign body granulomas at injection sites might be caused by PLGA. At the end of recovery phase, the above changes mostly recovered to normal, and on administering 3 mg/kg dose level once in 2 weeks on Beagle dogs showed no observed adverse effect. Taken together, RM had exhibited the acceptable safety.